斜齿轮高精度建模的安装误差对接触应力区域及齿根弯曲应力的影响 - 张发军; 周晓玲; 王杰; 李刚; 刘欣荣 (Jixie chuandong)
Based on the traditional modeling of helical gear,a high accuracy modeling method of involute helical gear is proposed based on Pro/E,the geometric accuracy of helical gear model is improved,the meshing process of contact is more close to the true gear tooth contact,and the accuracy of the analysis result is improved.At the same time,the law of contact stress of area variation with the installation error and the influence of installation error of helical gear on tooth root bending stress is studied,it is plays a certain guiding role on design,manufacturing,installation of the helical gear.